Approach of liberal Muslims toward religious text - Solihin, Sohirin Mohammad (2010)
Medical Law is a new and expanding field, which offers considerable scope for interdisciplinary study and collaboration. The responsibilities of those providing health care and the expectations of those receiving it are legally defined, and as a consequence the law is increasingly involved in dispute resolution. This challenging legal area draws on a wide range of existing legal subjects such as tort law, criminal law, family law and contract law. There is an increased interest among those involved in the medical field to know about the legal principles applicable to medical issues as there is now a developing pattern of judicial and legislative control over medical practice. Law and Ethics relating to the Medical Profession, authored by Dr Puteri Nemie Jahn Kassim, provides the principles of law and ethics governing medical issues such as consent to medical treatment, confidentiality, medical negligence, euthanasia, assisted reproduction, abortion, sterilisation and mental health. The book is designed not only to provide readers with thorough knowledge of the substantive medical law but also to enable readers to apply legal and ethical concepts to specific situations that relate to medical practice.